Enterprise Data Engineering: Architecting Modern Data Warehouses for Business Success - Dheeraj Kumar Bansal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article provides a comprehensive overview of Enterprise Data Engineering with a focus on Data Warehouse Architecture, exploring its critical role in modern organizations’ data strategies. It delves into the complexities of integrating diverse data sources, including point-of-sale systems, online databases, and CRM platforms. It examines the nuances of ETL/ELT processes essential for data integration. The article discusses various data warehouse architectures, compares cloud-based and on-premises solutions, and elaborates on dimensional modeling techniques crucial for effective data organization. It also covers creating and managing data marts, highlighting their importance in departmental analytics. The article emphasizes the significant benefits of enterprise data warehousing, including a unified data view, improved scalability, and enhanced decision-making capabilities. Furthermore, it addresses the critical aspects of data governance and quality. It explores advanced concepts such as data visualization, real-time processing, and AI and machine learning integration in data warehousing. This comprehensive exploration provides valuable insights for organizations seeking to leverage data as a strategic asset in the digital age.